2014
DOI: 10.15832/tbd.27845
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Stomatal Density and Distribution on Leaves of Turkish Hazelnut (Corylus avellana L.) Cultivars

Abstract: This study was carried out to determine stomatal distribution and density in leaves of 18 Turkish hazelnut cultivars. Stomata were detected only on the lower leaf surface (hypostomatous). The number of stomata varied between 83.08 (Kalınkara) and 117.73 (Sivri) per mm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
(3 reference statements)
3
7
0
1
Order By: Relevance
“…Stomatal distribution or also called stomata index is calculated from the ratio of the number of stomata to epidermal cells in a certain unit. The measurement method of stomatal distribution refers to Meidner & Mainsfield in Avci & Aygün [4] with the formula as follows: The number of stomatal and epidermal cells were counted from slide prepared using replica method. The number of stomata was counted under a microscope with 10x10 magnifications using a hand counter.…”
Section: Stomatal Distribution Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Stomatal distribution or also called stomata index is calculated from the ratio of the number of stomata to epidermal cells in a certain unit. The measurement method of stomatal distribution refers to Meidner & Mainsfield in Avci & Aygün [4] with the formula as follows: The number of stomatal and epidermal cells were counted from slide prepared using replica method. The number of stomata was counted under a microscope with 10x10 magnifications using a hand counter.…”
Section: Stomatal Distribution Calculationmentioning
confidence: 99%
“…Avci & Aygün [4] stated that the spread of stomata in the epidermis was influenced by variations in species and varieties in types and growing conditions. In addition, Juairiah [20] stated that differences in the distribution of stomata in each plant could be caused by genetic and phenotypic factors and are influenced by environmental factors.…”
Section: The Ratio Of Stomatal Distributionmentioning
confidence: 99%
“…İncelenen özelliklerdeki değişimin, genotip farklılığından kaynaklandığı düşünülmekle beraber, iklim ve toprak özelliklerindeki farklılıklar, yetiştiriciliğin yapıldığı alanın coğrafik durumu, hasat şekli ve zamanı, ürünün depolanması veya işlenmesi, uygulanan kültürel işlemlerin yöntem veya dönemsel olarak farklılığı gibi özellikler, ürünlerin son şekli ve içeriği üzerine önemli farklılıklara sebep olmaktadır (Gunes ve ark., 2006;Li ve ark., 2012;Tiwari ve Cummins, 2013;Avci ve Aygün, 2014;Gündüz ve Özbay, 2018).…”
Section: üMitvar Melez Bireylerin Tespitiunclassified
“…In addition, the number of stomata and stomatal properties affect gas exchange, photosynthesis production, drought resistance, and vegetative development (Çağlar & Tekin 1999;Çağlar et al 2004;Drake et al 2013). The number of stomata per unit area, stomata, and epidermis properties varies according to species and cultivars (Çağlar et al 2004;Akçin et al 2013;Avcı & Aygün 2014;Hurt & Doğan 2020). Although leaf micromorphological features such as cuticular wax types, and epidermal and stomatal properties have been used in the identification of plants, the literature survey has shown that no comprehensive study has yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…There are some data on leaf epidermis micromorphologies of the Corylus species. Uzunova (1999) investigated the leaf epidermis in European Corylaceae while Avcı & Aygün (2014) determined the stomata density and distribution in the leaves of 18 varieties of Turkish hazelnuts. There is, however, no data on the micromorphological properties of Turkish hazelnut cultivars.…”
Section: Introductionmentioning
confidence: 99%